Electrochemical Composite Formation of Polythiophene and Poly(N-Methylpyrrole) on CFME and Characterization with Electrochemical Impedance Spectroscopy - Geyik, Hulya; Sarac, Sezai; Parlak, Elif (The Electrochemical Society, 2006)
Abstract not Available.